Dobrilo Nenadić and native language heritage: Linguistic and educational context (on the example of the novel Vreme kokoški) - Petković Jelena L. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
The paper discusses the linguistic, stylistic and educational potential of the novel Vreme kokoški (2013) by Dobrilo Nenadić, part of whose oeuvre can be used to introduce native literature. The problem of student familiarization with the cultural heritage of the immediate community opens up, in order to build awareness of the values of one's own culture along with European values in education. The goal is to shed light on the peculiarities of the novel Vreme kokoški from a linguo-stylistic perspective, as well as to examine the possibilities of utilizing this novel in high school education to encourage students to become familiar with their native heritage. A qualitative research analysis was conducted using the technique of content analysis 1) on the corpus of scientific literature dealing with the works of Dobrilo Nenadić, as well as (2) on the corpus of one of the writer's works. This analysis showed that the application of native narrative prose in high school classes and extracurricular activities will enable: (1) students to become familiar with the idiolect of the native writer; (2) teachers to design student activities for researching native language heritage using a specific text. It is concluded that Nenadić's novel Vreme kokoški (2013), thanks to its linguistic and stylistic features and educational values, represents a stimulating work for secondary school teaching, especially for various extracurricular activities in the Serbian language.